2014
DOI: 10.1142/s0217732314501442
|View full text |Cite
|
Sign up to set email alerts
|

Orbital dynamics of the gravitational field of stringy black holes

Abstract: In this paper, we study the orbital dynamics of the gravitational field of stringy black holes by analyzing the effective potential and the phase plane diagram. By solving the equation of Lagrangian, the general relativistic equations of motion in the gravitational field of stringy black holes are given. It is easy to find that the motion of test particles depends on the energy and angular momentum of the test particles. Using the phase plane analysis method and combining the conditions of the stability, we di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Previously, this analysis has been successively applied on Schwarzschild [39] to describe its relativistic orbits. The relativistic orbits of stingy black holes [40] and regular Hayward black holes [41] have also been discussed by following the same phase-plane analysis. Inspired with the previous works on this topic so far, we are going to construct the relativistic orbits of the test particle in the gravitational field of Reissner-Nordström (RN) type regular black hole.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, this analysis has been successively applied on Schwarzschild [39] to describe its relativistic orbits. The relativistic orbits of stingy black holes [40] and regular Hayward black holes [41] have also been discussed by following the same phase-plane analysis. Inspired with the previous works on this topic so far, we are going to construct the relativistic orbits of the test particle in the gravitational field of Reissner-Nordström (RN) type regular black hole.…”
Section: Introductionmentioning
confidence: 99%
“…In order to explain the structure of geodesics better, the researchers have done a lot of work. Different research methods have been presented, including the effective potential analysis method [38][39][40] and the phase plane method [41][42][43][44]. By analyzing the behavior of effective potential, Juhua Chen et al [38] investigated the geodesics of particles in Horava-Lifshitz space-time [45], and Sheng Zhou et al [39] studied the time-like geodesic structure of the spherically symmetric black hole space-time [46].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is found that some solutions of the stringy theory can be considered as black hole (Cvetič and Youm 1996a,b), and this theory can combine the general relativity with the quantum field theory consistently. Therefore, the study of the stringy theory has been a hot point recently (Zhang et al 2014;Geng et al 2015;Li and Zhao 2015;Kuniyal et al 2015). Now, in the present paper, we would like to examine the accretion of dark energy onto the stringy electrically charged black hole.…”
Section: Introductionmentioning
confidence: 99%